NOVELLA SUÁREZ, Jorge (2021). La aventura del pensamiento español. Madrid: Sindéresis - Barroso Fernández, Oscar (Daimon Revista Internacional de Filosofia, 2023)
Reseña de NOVELLA SUÁREZ, Jorge (2021). La aventura del pensamiento español. Madrid: Sindéresis